Evaluación de los índices roproducitvos de marranas de la línea camborough 29, servidas por inseminación artificialy monta natural en Tarapoto - Escobar Vergaray, Floricelda (2016)
The present work of investigation entitled "Evaluation of the reproductive indexes of sows of the Camborough line 29, served by artificial insemination and mounted natural in Tarapoto city"; it had as objectives: Evaluating the reproductive indexes of the pig of the line Camborough 29 through artificial insemination and mounts into the company 'Natural R and R Saint Isidro C.C."; evaluating the days weaning-gestation; determining the percentage of death and birth of piglets by birth and the birth, fetal death and mummification by birth; with natural mating and artificial insemination. The parameters evaluated were: Days weaning-gestation; number of piglets born alive by birth; number of piglets born dead by birth; percentages of mortality; number of mummified. The results obtained indicate that: Regardless of the type of service (artificial or natural) in the days of weaning - covering these were statistically equal among themselves and in the second delivery is obtained the highest average with 7.5 days. With a natural service is obtained the highest number of piglets born alive with an average of 11.7 and which was increasing birth delivery. With the type of artificial service, we obtained the highest averages of percentage of piglets killed and percentage of mortality with 1.9% and 10.7% respectively, being superior statistically to the averages achieved with natural service, obviously the highest percentage of births was reached with the natural service with 97.6%. The percentage of mummy piglet births was quite low with 0.05% and 0.1% for natural service and artificial respectively. The number of births (from first to third) don’t represent statistical differences in the number of piglets killed, percentage of mortality, percentage of birth, and piglets born mummy